2021
DOI: 10.1369/00221554211041607
|View full text |Cite
|
Sign up to set email alerts
|

Independent of Calorie Intake, Short-term Alternate-day Fasting Alleviates NASH, With Modulation of Markers of Lipogenesis, Autophagy, Apoptosis, and Inflammation in Rats

Abstract: Non-alcoholic steatohepatitis (NASH) is a worldwide health problem. Alternate-day fasting (ADF), although thought to be aggressive, has proven safety and efficacy. We aimed to evaluate the effect of short-term ADF against already established high-fat-fructose (HFF)-induced NASH, independent of the amount of calorie intake, and to study the effect of ADF on lipogenesis, apoptosis, and hepatic inflammation. Male Sprague Dawley rats were divided into two groups: (1) negative control and (2) NASH group fed on HFF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Among these TKIs, Dasatinib exhibited prominent autophagy induction in A549 and PC-9 cell lines. Moreover, Elsayed et al [ 47 ] found that the induction of autophagy could attenuate high fat and fructose diet-induced hepatic injury. Furthermore, Sohn et al [ 48 ] stated that stimulation of autophagy by fatty diet rescued the kidney from injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among these TKIs, Dasatinib exhibited prominent autophagy induction in A549 and PC-9 cell lines. Moreover, Elsayed et al [ 47 ] found that the induction of autophagy could attenuate high fat and fructose diet-induced hepatic injury. Furthermore, Sohn et al [ 48 ] stated that stimulation of autophagy by fatty diet rescued the kidney from injury.…”
Section: Discussionmentioning
confidence: 99%
“…Serum glucose was detected using an Accu check blood glucose meter (Roche Diagnostic, Germany). MDA and GSH were measured following the technique of Elsayed et al (2021a , b) .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, low-carb diets have shown beneficial effects in reducing hepatic steatosis in humans [ 126 ]. Interestingly, using preclinical animal models, both calorie restriction and time-restricted feeding have been shown to induce hepatic autophagy [ 63 , 129 , 130 ].…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%